Physeter macrocephalus Linnaeus 1758 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Sperm Whale Physeter macrocephalus French: Grand Cachalot / German: Pottwal / Spanish: Cachalote Other common names: Cachalot, Pot Whale, Spermacet Whale Taxonomy. Physeter macrocephalus Linnaeus, 1758, “in Oceano Europao.” This species is monotypic. Distribution. Almost cosmopolitan, found from the edges of polar pack ice to the equator in both the Southern and Northern hemispheres. Descriptive notes. Total length 1520- 1920 cm (males) and 1040-1250 cm (females); up to more than 70,000 kg (males) and to 24,000 kg (females). Typical values are 1500 cm and 45,000 kg for males and 1100 cm and 15,000 kg for females. Sperm Whales are the most sexually dimorphic of all cetaceans in body length and weight. They are primarily dark gray, but skin can appear dark brown when viewed in bright sunlight. Their enormous head constitutes about 25-33%of animal’s total body length. A single blowhole is located asymmetrically on the left side at the front end of the rostrum. Twentyto 26 pairs ofconical teeth erupt only on the narrow, under-slung lower jaw. Small eyes are set far back on the head. Smooth skin occurs on head and flippers and appears dimpled past the eyes. Sperm Whales have flat, paddle-shaped flippers andlarge, triangular-shapedflukes with relatively straight trailing edges. Habitat. Deep, ice-free ocean waters across the globe, and in deep semi-enclosed seas (e.g. Mediterranean) but not enclosed seas (e.g. Black and Red). Female Sperm Whales and their dependent young generally inhabit tropical, subtropical, and temperate waters deeper than 1000 m and with sea surface temperatures greater than c.15°C. Subadult and adult males range more widely; the range oflarge adult males includes ice-free deep waters near both poles that may beclose to 0°C. Food and Feeding. Sperm Whales feed primarily on cephalopods. They are generalists, their prey being manyofthe larger, deep-ocean mesoand bathypelagic species. Preyincludes over 25 species of cephalopods, ranging from chiroteuthids weighing less than 100 g to giant squid ...